PENGARUH VARIASI TEKNIK UNTUK MENINGKATKAN KETERAMPILAN BANTINGAN PINGGANG BELA DIRI GULAT PADA USIA 15-18 TAHUN DI KLUB GULAT SMK NEGERI 1 KABANJAHE. - Moap Kasuramana Silverius Sinuraya; Deasyi Natalia Sitepu; Julius Boy Nesra Basgimata Barus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of technical variation training onimproving hip throw skills in wrestling athletes aged 15–18 years at theWrestling Club of SMK Negeri 1 Kabanjahe. The background of this study wasbased on the limited variation in training methods used in wrestling coaching,causing the athletes’ throwing skills to develop less optimally. Technicalvariation training was applied as an effort to improve movement adaptation,coordination, and the effectiveness of hip throw techniques. The researchmethod used was a quasi-experimental design with a One Group Pretest–Posttest Design. The population of this study consisted of all wrestling athletesaged 15–18 years at the Wrestling Club of SMK Negeri 1 Kabanjahe, totaling20 athletes. The sampling technique used was total sampling, so the entirepopulation was used as the research sample. The research instrument was ahip throw skill test assessed based on technique accuracy, pushing power,movement coordination, execution speed, and opponent landing control. Thedata were analyzed using descriptive statistics, normality tests, and pairedsample t-tests. The results showed that the average pretest score of 14.60increased to 20.95 in the posttest. The percentage increase in hip throw skillswas 43.49%. The t-test results showed that the calculated t-value was 20.03,which was greater than the t-table of 2.093 at a significance level of 0.05 with19 degrees of freedom. Therefore, the alternative hypothesis (H1H_1H1) wasaccepted, indicating that there was a significant effect of technical variationtraining on improving the hip throw skills of wrestling athletes aged 15–18 yearsat the Wrestling Club of SMK Negeri 1 Kabanjahe. Based on the results of thisstudy, it can be concluded that technical variation training is effective inimproving the hip throw skills of adolescent wrestling athletes. This study isexpected to serve as a reference for coaches in designing more varied,effective, and developmentally appropriate training programs for young athletes